Oral manifestations in children with congenital Zika virus syndrome: a systematic review - Maria Júlia Delsin Gallo; Kelly Fernanda Molena; Thalia Carvalho de Almeida dos Santos; Fabrício Kitazono de Carvalho; Francisco Wanderley Garcia Paula e Silva; Murilo Fernando Neuppmann Feres; Alexandra Mussolino de Queiroz (SpringerOpen, 2024)
Abstract Background Congenital Zika Syndrome (CZS) comprises congenital anomalies that occur in individuals, embryos or fetuses exposed to Zika virus infection during pregnancy and can result in systemic manifestations as well as alterations in the oral cavity of these children. The aim of this study was to conduct a systematic literature review of the most frequent oral and craniofacial manifestations in children aged 0 to 6 years with CZS compared to neurotypical children without CZS. Main body of the abstract In this review, a search was conducted in the PubMed, Medline, Embase, Web of Science databases and grey literature, as well as a manual search of the reference lists of the included articles, without restriction on year or language. Inclusion criteria were studies reporting oral alterations in children up to six years old or newborns with CZS, with or without a control group. Methodological quality of the studies was assessed by the Mixed Methods Appraisal Tool (MMAT). Twenty-seven articles were retrieved, 19 quantitative non-randomized and 09 quantitative descriptive studies. Three studies presented a high risk of bias. The main reported manifestations were delayed eruption (51,8%), dental enamel defects (25,9%), deep palate (29,6%), number alterations (14,8%), bruxism (29,6%), and malocclusion (25,9%). Short conclusion CZS can lead to several manifestations of dental interest and may interfere with the individual's oral health. The pediatric dentistry thus requiring the dentist to be attentive to these changes to offer the best and comprehensive treatment to this patient.